Structural Evolution in Wet Mechanically Alloyed Co-Fe-(Ta,W)-B Alloys - Vladimír Girman; Maksym Lisnichuk; Daria Yudina; Miloš Matvija; Pavol Sovák; Jozef Bednarčík (Metals, 2021)
In the present study, the effect of wet mechanical alloying (MA) on the glass-forming ability (GFA) of Co<semantics>43</semantics>Fe<semantics>20</semantics>X<semantics>5.5</semantics>B<semantics>31.5</semantics> (X = Ta, W) alloys was studied. The structural evolution during MA was investigated using high-energy X-ray diffraction, X-ray absorption spectroscopy, high-resolution transmission electron microscopy and magnetic measurements. Pair distribution function and extended X-ray absorption fine structure spectroscopy were used to characterize local atomic structure at various stages of MA. Besides structural changes, the magnetic properties of both compositions were investigated employing a vibrating sample magnetometer and thermomagnetic measurements. It was shown that using hexane as a process control agent during wet MA resulted in the formation of fully amorphous Co-Fe-Ta-B powder material at a shorter milling time (100 h) as compared to dry MA. It has also been shown that substituting Ta with W effectively suppresses GFA. After 100 h of MA of Co-Fe-W-B mixture, a nanocomposite material consisting of amorphous and nanocrystalline bcc-W phase was synthesized.